Encapsulation of bioactive compounds from Sargassum ilicifolium: Influence of wall material type and loading content on the physicochemical and structural properties of microparticles - Seyed Saeed Sekhavatizadeh; Mohammad Ganje; Seyedeh Sedigheh Hashemi; Mohammad Reza Mozafarian (Heliyon)
Sargassum brown seaweed (Sargassum ilicifolium) is reported to exhibit several biological activities that promote human health, but it does not have the ability to withstand harsh environmental conditions, such as high temperatures and oxygen exposure. Encapsulation of Sargassum ilicifolium extraction through different techniques is known to, optimize physicochemical properties, biological activities, maintain stability, and is an effective way to improve the shelf life of different foods. In the present study, the encapsulation of SIE was carried out by the freeze-drying method using maltodextrin, whey protein isolate (WPI), and chitosan. The bioactive compound of SIE, encapsulation efficiency, and the structural properties of microparticles were analyzed. The evaluations indicated carotenoid (0.77 ± 0.22 mg/g), phenol (0.12 ± 0.02 mg/mL), and flavonoid compounds (4.03 ± 0.28 mg GA/Eg) in the extract, respectively. According to the results, the mixtures of algae extracts prepared with the combination of WPI and MD were more stable and had a lower viscosity than the other treatments. The highest (99.26 %) and lowest (13.41 %) encapsulation efficiencies were obtained for WPI (30 %), MD (70 %), with a 1:12 ratio of SI to wall, and chitosan, with a 1:8 ratio of SI to wall, respectively. X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and Scanning electron microscopy (SEM) confirmed the entrapment of the SIE in the beads. Finally, the improved stability and solubility characteristics of the SIE powder, which is based on WPI and maltodextin, indicate its potential for use as a potent functional food additive.